A COMPARATIVE STUDY ON USING THE PERSUASIVE POWER OF PERSON DEIXIS IN POLITICAL AND RELIGIOUS TEXTS - Zainab Abbodi Ali, Researcher; Rana H. Al-Bahrani, Assistant Professor Dr. (lark, 2026)
Addressing issues related to the implied meaning of expressions and words are dealt with using pragmatics. Deixis is a case in point; it refers to a type of reference that offers the reader a deeper understanding of what characters intend by their utterances. This research is qualitative in nature; it aims to examine comparatively the prevalent type of deictic words invested in political and religious texts, and to investigate the reasons behind their usage in such contexts. To meet this objective, two speeches have been selected; one is political belonging to the American President Barack Obama, and the second one is religious belonging to Muzammil Sidiqi, an Indian director of the Islamic Center of Washington, D.C. The study has concluded that both politicians and preachers employ different types of deictic markers in their writings. However, it has been noted that politicians utilize deictic words and expressions, such as the 1st person, specifically (we), in political texts more frequently than preachers owing to personal and political objectives, to garner support during elections and to assert dominance, particularly among the American politicians. Conversely, preachers use the 1st person (we) for advice and guidance purposes, aiming to direct the audience towards the correct religious path and to foster a sense of belonging within the Muslim community, emphasizing as a result the need for guidance and advice. This is because both preachers and individuals should strive to be closer to Allah through obedience.
Keywords: Deixis, person deixis, persuasive power, political text, religious text, qualitative study